PENGARUH PENGGUNAAN MODEL THINK PAIR SHARE TERHADAP KEMAMPUAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP N 5 KOTO XI TARUSAN - Widya Eka Putri; Ricci Gemarni Tatalia; Suci Dwinitia (Sekolah Tinggi Pariwisata Mataram, 2021)
This research is motivated by the following problems. First, students are still not skilled in writing the Observation Result Report text. Second, the difficulty in determining the existing structure in the text of the Observation Result Report. This study aims to describe the effect of using the Think Pair Share learning model on the Ability to Write Text on Observation Results of Class VII Students of SMP N 5 Koto XI Tarusan. This type of research is quantitative research. The sample in this study were students of class VII SMP N 5 Koto XI Tarusan, totaling 26 people. The data in this study were the score of the ability to write text on the Observation Result Report before using the Think Pair Share Model and the score for the ability to write the text of the Observation Result Report after using the Think Pair Share learning model for seventh grade students of SMP N 5 Koto XI Tarusan. The results of this study can be concluded as follows. First, the ability to write a text report on the observation results of class VII students of SMP N 5 Koto XI Tarusan before using the Think Pair and Share learning model obtained an average score of 74.35 with a qualification of more than more than enough (LdC). Second, the ability to write a text report on the observation results of class VII students of SMP N 5 Koto XI Tarusans, after using the Think Pair and Share learning model, got an average score of 80.76 with good qualifications (B). Third, based on the results of the t-test, it was obtained tcount> ttable (2.18> 1.71). So, it can be concluded that the use of the Think Pair and Share learning model has an effect on the ability to write a text on the observation report of grade VII students of SMP N 5 Koto XI Tarusan